School-scape as a linguistic battlefield: an LL study at Darussalam education complex of Gontor, Indonesia - Zuliati Rohmah; Diana Nur Sholihah; Yazid Basthomi; A. Dzo’ul Milal (Cogent Arts & Humanities)
The current linguistic landscape study aims to analyze the multilingualism aspects observable in the school-scape of an exemplary institution of Darussalam Islamic Educational Complex of Gontor. A descriptive research project, this study obtained the data from both top-down and bottom-up signs visible in public places within the educational complex; thus, only signs apparent from outside of buildings totaling 148 signs were analyzed. The data analysis shows that there are four languages observable in the vicinity with English and Arabic as the most often employed languages. This situation shows a strong loyalty the institution’s language policy. Although the educational complex is a multilingual community, multilingual signs are the least among the public signs. Most of the signs are monolingual signs of either English or Arabic. The enacted language policy provides bigger rooms for English and Arabic to be visible in the school-scape, which leads to the subsumption of the national language of Bahasa Indonesia and the local language of Javanese. This condition reveals their pragmatic concern to empower the students to be ready for various facets of international life. As such, this study informs the school management about the value of the linguistic diversity and offer insights that potentially guide the development of educational strategies that leverage the linguistic landscape as a source for language learning and cultural enrichment. The findings also inform government policymakers about the importance of linguistic diversity in educational settings.